DOI: 10.31979/etd.58wj-dk5q
|View full text |Cite
|
Sign up to set email alerts
|

Professional Learning Community (PLC)

Abstract: Research Question #2: What are the aspects of the PLC that facilitate to teachers' innovative practices related to addressing the digital use divide?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
(170 reference statements)
2
2
0
Order By: Relevance
“…The results in Table 2 also show that professional learning communities have the potential to enhance high school teacher's capacity to use multimedia technologies to deliver lessons online (M = 4.05). This finding concurs with the work of Cheng (2017) who advances that professional learning communities are vital to positively influence teacher technology use behavior. Professional learning community participation and blended teaching enhancement items on the questionnaire were computed resulting in a minimum possible score of 1 and maximum of 5.…”
Section: Relationship Between Professional Learning Community Partici...supporting
confidence: 90%
“…The results in Table 2 also show that professional learning communities have the potential to enhance high school teacher's capacity to use multimedia technologies to deliver lessons online (M = 4.05). This finding concurs with the work of Cheng (2017) who advances that professional learning communities are vital to positively influence teacher technology use behavior. Professional learning community participation and blended teaching enhancement items on the questionnaire were computed resulting in a minimum possible score of 1 and maximum of 5.…”
Section: Relationship Between Professional Learning Community Partici...supporting
confidence: 90%
“…The third finding revealed that PTL directly affects the SDC (H3), encompassing dimensions such as OL and PLCs. This is consistent with prior studies regarding the significance of communication and collaboration among teachers within the school culture for effecting sustainable changes in educational organizations, where the principal's leadership plays a crucial role [54,58,67,97,129,130]. This implies that effectively implementing the principal's technology leadership in schools can foster an environment where teachers actively seek information, communicate, and collaborate, leveraging technology tools as facilitators.…”
Section: Direct Effectsupporting
confidence: 89%
“…Numerous studies and investigations have explored the importance of principal technology leadership in developing a school's digital culture [29,[58][59][60]. This, in turn, directly affects the teacher's digital skills in technology integration [61][62][63][64][65][66].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation